Light-transmitting slurry and preparation method and application thereof, light-transmitting artificial stone and preparation method and application thereof
By using a specific ratio of light-transmitting slurry, the existing light-transmitting artificial stones have been solved, and the problems of large material loss, unnatural light-transmitting effect and poor interface adhesion during processing are achieved, and the quality stability of light-transmitting artificial stones and the naturalness of light-transmitting effect are achieved, improving the overall performance of the board.
Patent Information
- Application Number
- CN202510193535.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the processing process, existing light-transmitting artificial stones have problems such as large material loss, unnatural light-transmitting effect, and easy to cause crushing, bending and displacement of materials. Moreover, the physical and chemical properties of the transmissive materials and the matrix materials are large, resulting in poor interface adhesion, affecting the waterproof, pollution resistance and decorative performance of the board.
A light-transmitting slurry is used, including adhesives, light-transmitting fillers, shrinkage agents, interface treatment agents, penetration agents and initiators. Through specific ratios and processes, the fluidity, permeability and transparency of the slurry are improved, and cured at high temperatures, so that its physical and chemical properties are close to that of artificial stone substrate materials and enhance the interface adhesion with the substrate materials.
It realizes the quality stability of light-transmitting artificial stone and the naturalness of light-transmitting effect, solves the problems of material displacement, damage and interruption during the pressing process, improves the waterproof, pollution resistance and decorative performance of the board, and simplifies the process flow, which is suitable for industrial production.
Smart Images

Figure CN119662166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light-transmitting artificial stone, and in particular to a light-transmitting slurry and a preparation method and application thereof, and a light-transmitting artificial stone and a preparation method and application thereof. Background Art
[0002] Artificial stone is made of inorganic hydraulic cementitious materials or organic polymer materials as adhesives, adding quartz powder, calcium powder, fly ash, silica fume and other admixtures, as well as quartz sand, calcium sand, coarse aggregate and various additives, in a certain proportion and through a certain process. With the continuous depletion of natural stone resources, artificial stone, as a new green, environmentally friendly and decorative material, has been widely used and paid attention to in the context of the rapid development of the construction industry and the urgent demand for green and environmentally friendly materials.
[0003] In recent years, functional artificial stones have developed rapidly, such as antibacterial artificial stones, luminous artificial stones, and color-changing artificial stones, which have been widely used in special fields. Translucent artificial stones have advantages in terms of personalized decorative design and translucent functional requirements, such as personalized translucent patterns, line markings, and translucent energy storage, and have broad application prospects.
[0004] At present, the translucent materials used in translucent artificial stones are mostly optical fibers, resin strips, glass and other materials with translucent properties. They are in the form of solid wires, cables, tubes or rods. One method is to pre-implant them during the production process of the board, and the other method is to drill holes and embed them after the board is formed. There are the following problems: (1) The processing is complicated. The translucent materials used are in the form of solid wires, cables, tubes or rods, and need to be cut according to the thickness of the board; (2) The material loss is large. The translucent materials need to be cut according to the thickness of the board, which will form a large number of scraps of inappropriate size, resulting in a waste of resources; (3) The cross-sectional shape of the translucent material is fixed and single. The translucent aperture is mostly fixed in the form of a circle and other regular triangles and quadrilaterals, which are regular and regular. The translucent effect is unnatural and rigid; (4) Due to human factors, the light-transmitting effect is not natural and is relatively rigid. The pressing process of artificial stone slabs is a high-frequency vibration pressing process, so the translucent material is prone to problems such as breaking, bending and displacement; (5) The physical and chemical properties between the translucent material and the base material are quite different, and there are large differences in linear expansion coefficient, compressive strength and bending strength. When the board is under load and in a large temperature difference environment, the translucent material and the base material deform differently, causing the translucent material and the base material to fall off or be squeezed and damaged; (6) The surface of the translucent material is relatively smooth, and the interface adhesion between it and the base material is poor. The volume of the base material of the artificial stone slab will change to a certain extent during solidification, and under the adjustment of the above (5), the translucent material and the base material are more likely to fall off, forming interface pores, thereby affecting the waterproof, pollution-resistant and decorative properties of the artificial stone slab.
[0005] The Chinese invention patent application with application number CN202410080933.X discloses a light-transmitting inorganic artificial stone and a preparation method thereof. In the process of producing inorganic artificial stone by the pressing plate method, holes are punched on a wooden base plate according to the desired pattern, and then PMMA light-transmitting fibers are inserted into the base plate holes. This method is complex to operate, has a large workload, and is time-consuming and labor-intensive to implement. First, the aperture position and aperture size must be accurately controlled. The aperture position deviation will affect the pattern effect. The aperture size deviation will make it impossible to insert the light-transmitting fiber into the aperture or the fit will not be firm and it will easily fall off. If the optical fiber is too thin, the operation will be more difficult and it will be easy to bend. The wooden base plate is placed at the bottom of the mold, and the mixture is evenly spread over the mold. Since the artificial stone slurry is in a semi-dry and wet state and most products contain coarse-grained aggregates, it is difficult to evenly distribute the slurry around the light-transmitting optical fiber, and it is easy to produce material shortage and void problems. The pressing process is high-frequency vibration pressing, and the light-transmitting optical fiber is prone to quality problems such as breaking, bending, and displacement. The wooden base plate mold used to fix the optical fiber is easily damaged and contaminated and cannot be reused.
[0006] The Chinese invention patent application with application number CN202310474743.1 discloses a luminous and permeable 3D printed concrete material and a construction method thereof. The light-guiding material is selected from wires, cables, tubes or rod-shaped materials made of optical fibers, resins, glass or acrylic materials. The light-guiding connector is used to connect the light-guiding materials along the arrangement direction, along the strip direction and along the stacking direction to complete a continuous light-guiding skeleton. The construction method of the 3D printed concrete material is used to continuously and integratedly place the light-guiding material during the printing process along the arrangement direction and along the strip direction. Since the light-guiding material is laid by pouring, it is easy to have the problem of discontinuity of the light-guiding material, blocking the light-guiding performance. At the same time, when the light-guiding materials are continuous and without gaps, there is no cementitious material bonding between the light-guiding materials, and the structural firmness and strength cannot be guaranteed. In the process of pouring the slurry, due to the downward impact force of the slurry under the action of gravity and pumping pressure, it is easy to disperse the light-guiding materials that are closely arranged together to form a cross section, affecting the continuity of the light guide.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] One of the purposes of the present invention is to provide a light-transmitting slurry with high fluidity, good permeability and transparency, which can be cured at high temperature and has physical and chemical properties close to those of artificial stone matrix materials, which is beneficial to improving the interface adhesion between the artificial stone matrix and the artificial stone matrix.
[0009] The second object of the present invention is to provide a method for preparing a light-transmitting slurry, which has a simple process, high efficiency, high success rate and is suitable for industrial production.
[0010] The third object of the present invention is to provide an application of a light-transmitting slurry, which can not only improve the quality stability of the light-transmitting artificial stone, which is conducive to forming a dense artificial stone slab, but also make the light transmission of the artificial stone more natural.
[0011] A fourth object of the present invention is to provide a light-transmitting artificial stone with stable quality and more natural light transmission.
[0012] The fifth object of the present invention is to provide a method for preparing light-transmitting artificial stone, which can solve the problems of displacement, breakage and discontinuity of the light-transmitting materials used in the prior art during the pressing process, as well as the problem of unnatural and rigid light transmission.
[0013] A sixth object of the present invention is to provide an application of light-transmitting artificial stone, which is beneficial to improving the decorative effect of buildings and can meet more decorative scene design requirements.
[0014] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a light-transmitting slurry comprises the following components by weight: 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treatment agent, 0.05-0.2 parts of penetrant, and 0.01-0.05 parts of initiator; The adhesive is mainly prepared from the following components by weight: 5-20 parts of polymethyl methacrylate, 1-5 parts of methyl acrylate, 30-60 parts of methyl methacrylate, 1-5 parts of hydroxyethyl acrylate, 1-5 parts of trimethylolpropane trimethacrylate, and 0.01-0.05 parts of initiator.
[0015] Further, the light-transmitting filler includes at least one of glass microspheres and meteorological silica; The shrinkage reducing agent includes neopentyl glycol; The interface treatment agent includes at least one of stearic acid, phthalate ester and phosphate ester; The penetrant includes at least one of sodium fatty alcohol polyoxyethylene ether sulfate, ammonium fatty alcohol polyoxyethylene ether sulfate and sodium lauryl sulfate; The initiator includes methyl ethyl ketone peroxide.
[0016] Furthermore, the preparation method of the adhesive comprises the following steps: The components are mixed in proportion to carry out polymerization reaction, and when the viscosity of the product obtained by the polymerization reaction reaches 80mpa.s-150mpa.s, a polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The polymerization reaction temperature is 75°C-85°C; The polymerization inhibitor includes hydroquinone.
[0017] In a second aspect, a method for preparing the light-transmitting slurry as described in any one of the above items comprises the following steps: By weight, 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treating agent, 0.05-0.2 parts of penetrant and 0.01-0.05 parts of initiator are mixed to obtain the light-transmitting slurry.
[0018] A third aspect provides an application of the light-transmitting slurry described in any one of the above items in light-transmitting artificial stone.
[0019] In a fourth aspect, a light-transmitting artificial stone is prepared by using any of the light-transmitting slurries described above.
[0020] In a fifth aspect, a method for preparing the above-mentioned light-transmitting artificial stone comprises the following steps: (a) preparing a matrix slurry by a grading method, taking the matrix slurry for spreading, pressing, and obtaining an embryo body; (b) spreading the light-transmitting slurry on the light-transmitting area of the embryo body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain the light-transmitting artificial stone.
[0021] Furthermore, the matrix slurry is prepared by the following components in parts by weight: 20-50 parts of quartz sand of 26-40 mesh, 20-50 parts of quartz sand of 40-70 mesh, 2-4 parts of unsaturated polyester resin, 1-5 parts of pigment, curing agent, and coupling agent; Among them, the amount of curing agent accounts for 0.5%-2.0% of the amount of unsaturated polyester resin; The amount of coupling agent used accounts for 0.5%-2.0% of the amount of unsaturated polyester resin; The porosity of the artificial stone designed in the above-mentioned broken gradation mode is 10%-20%.
[0022] Furthermore, the light-transmitting slurry penetrates and fills the pores of the light-transmitting area under the action of negative pressure; The curing temperature is 90° C.-110° C., and the curing time is 2 h-3 h.
[0023] A sixth aspect is an application of the above-mentioned light-transmitting artificial stone in architectural decoration.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects: The light-transmitting slurry provided by the present invention not only adjusts the uniformity and stability of the light-transmitting slurry system through the viscosity of the specific adhesive, but also has the characteristics of high fluidity, good permeability and good transparency, and can be cured at high temperature; with the coordinated cooperation of various components and their proportions, the physical and chemical properties of the light-transmitting slurry are basically consistent with those of the artificial stone matrix material, and the interface bonding force between the light-transmitting slurry and the matrix material is strong.
[0025] The method for preparing the light-transmitting slurry provided by the invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0026] The application of the light-transmitting slurry provided by the present invention can not only improve the quality stability of the light-transmitting artificial stone, which is conducive to forming a dense artificial stone plate, but also can make the light transmission of the artificial stone more natural.
[0027] The light-transmitting artificial stone provided by the present invention has stable quality and more natural light transmission.
[0028] The preparation method of the light-transmitting artificial stone provided by the present invention uses a discontinuous gradation method to design a board formula so that a light-transmitting area is formed on the board, and is combined with a specific light-transmitting slurry. Not only is the preparation method simple, but also different light-transmitting effects can be designed, such as light-transmitting intensity, light-transmitting area, light-transmitting diameter, and light-transmitting color. Specifically, a matrix slurry with a discontinuous gradation design is used for laying, so that a three-dimensional structure of interlinked and interwoven pores is formed in the board, which is water-permeable and light-permeable, and is filled with a light-transmitting slurry after solidification. After solidification, the light-transmitting slurry will be tightly bonded to the matrix material. , thereby forming a dense artificial stone plate. When a light source is irradiated on one side of the plate, the light will be transmitted to the other side of the plate along the resin body that is interconnected and interwoven inside, and the plate has a natural light transmission effect. In short, the preparation method of the present invention is not only simple to operate, low in cost, and high in production efficiency, but also conducive to product promotion and application. Moreover, the light transmission aperture size and area range can be arbitrarily designed and easy to achieve, and the light transmission effect is more natural. This solves the problem that the prior art uses light-transmitting materials that will be displaced, damaged, and discontinuous during the pressing process, and that the light transmission is unnatural and relatively rigid.
[0029] The application of the light-transmitting artificial stone provided by the present invention is conducive to improving the decorative effect of buildings and can meet more decorative scene design requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1A physical picture of a light-transmitting artificial stone with full-area light transmission provided by an embodiment of the present invention; Figure 2 A physical picture of a light-transmitting artificial stone with partial light transmission provided by an embodiment of the present invention; Figure 3 A light transmission effect diagram of full-area light transmission provided by an embodiment of the present invention; Figure 4 This is a light transmission effect diagram of a local area provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] According to a first aspect of the present invention, there is provided a light-transmitting slurry comprising the following components in parts by weight: 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treatment agent, 0.05-0.2 parts of penetrant, and 0.01-0.05 parts of initiator; Among them, the typical but non-limiting weight portions of the adhesive are, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, and 60 parts; the typical but non-limiting weight portions of the light-transmitting filler are, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts; the typical but non-limiting weight portions of the shrinkage reducing agent are, for example, 0.05 parts, 0.1 parts, 0.15 parts, and 0.2 parts; the typical but non-limiting weight portions of the interface treatment agent are, for example, 0.05 parts, 0.1 parts, 0.15 parts, and 0.2 parts; the typical but non-limiting weight portions of the penetrant are, for example, 0.05 parts, 0.1 parts, 0.15 parts, and 0.2 parts; the typical but non-limiting weight portions of the initiator are, for example, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, and 0.05 parts; The adhesive is mainly prepared from the following components in parts by weight: 5-20 parts of polymethyl methacrylate, 1-5 parts of methyl acrylate, 30-60 parts of methyl methacrylate, 1-5 parts of hydroxyethyl acrylate, 1-5 parts of trimethylolpropane trimethacrylate, and 0.01-0.05 parts of initiator; Among them, typical but non-limiting weight portions of polymethyl methacrylate are, for example, 5 parts, 10 parts, 15 parts, and 20 parts; typical but non-limiting weight portions of methyl acrylate are, for example, 1 part, 2 parts, 3 parts, 4 parts, and 5 parts; typical but non-limiting weight portions of methyl methacrylate are, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, and 60 parts; typical but non-limiting weight portions of hydroxyethyl acrylate are, for example, 1 part, 2 parts, 3 parts, 4 parts, and 5 parts; typical but non-limiting weight portions of trimethylolpropane trimethacrylate are, for example, 1 part, 2 parts, 3 parts, 4 parts, and 5 parts; typical but non-limiting weight portions of initiator are, for example, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, and 0.05 parts.
[0034] The light-transmitting slurry provided by the present invention not only adjusts the uniformity and stability of the light-transmitting slurry system through the viscosity of the specific adhesive, but also has the characteristics of high fluidity, good permeability and good transparency, and can be cured at high temperature; with the coordinated cooperation of various components and their proportions, the physical and chemical properties of the light-transmitting slurry are basically consistent with those of the artificial stone matrix material, and the interface bonding force between the light-transmitting slurry and the matrix material is strong.
[0035] In the present invention, since the light-transmitting slurry and the artificial stone base material are similar in key indicators such as linear expansion coefficient, compressive strength and bending strength, the light-transmitting material can maintain basically consistent deformation with the base material under stress load and in a large temperature difference environment, effectively avoiding the problem of the light-transmitting material and the base material falling off or being squeezed and damaged.
[0036] In a preferred embodiment, the light-transmitting filler may be a highly light-transmitting powder, including but not limited to at least one of glass microspheres and meteorological silica.
[0037] In the present invention, the shrinkage reducing agent includes but is not limited to neopentyl glycol.
[0038] In a preferred embodiment, the interface treatment agent includes but is not limited to at least one of stearic acid, phthalate esters and phosphate esters, which is more conducive to improving the interface bonding strength between the light-transmitting slurry and the base material.
[0039] In a preferred embodiment, the penetrant includes but is not limited to at least one of sodium fatty alcohol polyoxyethylene ether sulfate, ammonium fatty alcohol polyoxyethylene ether sulfate and sodium dodecyl sulfate.
[0040] Adding specific additives to the light-transmitting slurry can effectively improve the interfacial bonding strength between the light-transmitting slurry and the base material, which can avoid the problem of falling off and forming interface pores between the light-transmitting slurry and the base material, and is beneficial to improving the waterproof, pollution-resistant and decorative properties of artificial stone panels.
[0041] In addition, ultraviolet light absorbers and anti-aging agents can be added to the light-transmitting slurry, which can effectively improve the aging resistance of the slurry and help to increase its service life.
[0042] In a preferred embodiment, the adhesive used in the light-transmitting slurry can be prepared by the following method: The components are mixed in proportion to carry out polymerization reaction. When the viscosity of the product obtained by the polymerization reaction reaches 80mpa.s-150mpa.s, a polymerization inhibitor is added to terminate the polymerization reaction to obtain an adhesive; The polymerization temperature may be 75°C-85°C, with typical but non-limiting examples being 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C; The polymerization inhibitor includes but is not limited to hydroquinone.
[0043] A typical preparation method of an adhesive comprises the following steps: By weight, 5-20 parts of polymethyl methacrylate (PMMA), 1-5 parts of methyl acrylate, 30-60 parts of methyl methacrylate, 1-5 parts of hydroxyethyl acrylate, 1-5 parts of trimethylolpropane trimethacrylate and 0.01-0.05 parts of methyl ethyl ketone peroxide initiator were stirred and mixed to cause polymerization reaction. The stirring speed was set to 40r / min-60r / min, and the temperature was raised to 7 at a uniform speed of 2℃ / min-5℃ / min. 5℃-85℃, with the continuous dissolution of PMMA and the continuous polymerization of active monomers, the viscosity of the obtained resin product continues to increase. When its viscosity reaches 80mpa.s-150mpa.s, hydroquinone is added as an inhibitor (0.01 parts-0.05 parts), the stirring speed is set to 60r / min-80r / min, and the temperature is uniformly lowered to 25℃-35℃ by 10℃ / min-20℃ / min to terminate the polymerization reaction, and stirring is continued for 30 minutes to obtain an adhesive.
[0044] According to a second aspect of the present invention, there is provided a method for preparing the light-transmitting slurry as described in any one of the above items, comprising the following steps: By weight, 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treating agent, 0.05-0.2 parts of penetrant and 0.01-0.05 parts of initiator are mixed to obtain light-transmitting slurry.
[0045] The method for preparing the light-transmitting slurry provided by the invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0046] A typical preparation method of a light-transmitting slurry comprises the following steps: Calculated by weight, 30-60 parts of adhesive, 5-10 parts of translucent filler, 0.05-0.2 parts of neopentyl glycol (shrinkage reducing agent), 0.05-0.2 parts of interface treatment agent, 0.05-0.2 parts of penetrant and 0.01-0.05 parts of methyl ethyl ketone peroxide (initiator) are added to a high-speed disc disperser with a rotation speed of 150r / min-200r / min, and stirred and dispersed for 30 minutes to obtain a translucent slurry.
[0047] According to a third aspect of the present invention, there is provided a use of the light-transmitting slurry described in any one of the above items in light-transmitting artificial stone.
[0048] The application of the light-transmitting slurry provided by the present invention can not only improve the quality stability of the light-transmitting artificial stone, which is conducive to forming a dense artificial stone plate, but also can make the light transmission of the artificial stone more natural.
[0049] According to a fourth aspect of the present invention, there is provided a light-transmitting artificial stone, which is prepared by using any of the light-transmitting slurries described above.
[0050] The light-transmitting artificial stone provided by the present invention has stable quality and more natural light transmission.
[0051] According to a fifth aspect of the present invention, there is provided a method for preparing the above-mentioned light-transmitting artificial stone, comprising the following steps: (a) preparing a matrix slurry by a grading method, taking the matrix slurry for spreading, pressing, and obtaining an embryo body; (b) spreading the light-transmitting slurry to the light-transmitting area of the embryo body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain a light-transmitting artificial stone.
[0052] The preparation method of the light-transmitting artificial stone provided by the present invention designs the board formula by using the discontinuous grading method, so that a light-transmitting area is formed on the board, and is combined with a specific light-transmitting slurry. Not only is the preparation method simple, but also different light-transmitting effects can be designed, such as light-transmitting intensity, light-transmitting area, light-transmitting aperture and light-transmitting color. Specifically, the base slurry with discontinuous grading design is used for laying, so that a three-dimensional structure of interlinked and interwoven pores is formed in the board, which is permeable to water and light, and is filled with a light-transmitting slurry after curing. After curing, the light-transmitting slurry will be tightly bonded to the base material, thereby forming a dense artificial stone board. When a light source is irradiated on one side of the board, the light will be transmitted to the other side of the board along the internal interlinked and interwoven resin body, and the board has a natural light-transmitting effect.
[0053] In summary, the preparation method of the present invention is not only simple to operate, low in cost, and high in production efficiency, which is conducive to the promotion and application of products, but also the light-transmitting aperture size and area range can be arbitrarily designed and easily realized, for example, the light-transmitting artificial stone can be fully or partially transparent. Figure 1 and Figure 2 , light transmission effects are shown in Figure 3 and Figure 4 The light transmission effect is more natural, which solves the problems of displacement, breakage and discontinuity in the pressing process of the light-transmitting materials in the prior art, and the problem of unnatural and rigid light transmission.
[0054] In the present invention, the porosity of the artificial stone designed in a discontinuous gradation manner may be 10%-20%.
[0055] In a preferred embodiment, the light-transmitting slurry can penetrate into and fill the pores of the light-transmitting area under the action of negative pressure.
[0056] In a preferred embodiment, the curing temperature of the light-transmitting slurry can be 90°C-110°C, and typical but non-limiting temperatures are, for example, 90°C, 95°C, 100°C, 105°C, and 110°C. The curing time can be 2h-3h, and typical but non-limiting times are, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h, and 3h, which is more conducive to obtaining a dense artificial stone slab.
[0057] A typical preparation method of light-transmitting artificial stone comprises the following steps: (a) preparing the matrix slurry by discontinuous grading, designing the porosity of the artificial stone to be 10%-20%, specifically, by weight, putting 20-50 parts of quartz sand of 26-40 mesh, 20-50 parts of quartz sand of 40-70 mesh, 2-4 parts of unsaturated polyester resin, 1-5 parts of pigment, curing agent and coupling agent into a mixer and stirring for 3-5 minutes to obtain the matrix slurry; Among them, the amount of curing agent (methyl ethyl ketone oxide) can account for 0.5%-2.0% of the amount of unsaturated polyester resin; the amount of coupling agent (KH570) can account for 0.5%-2.0% of the amount of unsaturated polyester resin; The obtained matrix slurry is evenly distributed on a mold with a frame, and then sent to a press for pressing (press parameters: vibration frequency 250Hz, vacuum degree 0.75bar, pressure 2MPa), and after pressing, a board embryo is obtained; (b) First, pour the light-transmitting slurry evenly on the surface of the board body, then apply it evenly with a brush, and then send it into a press (which can be vacuumed) or a vacuum box and turn on the vacuum pump to perform vacuum treatment. The light-transmitting slurry will penetrate into the pores under the action of negative pressure, completing the light-transmitting slurry spreading; (c) After the light-transmitting slurry is applied, the board is placed at 90°C-110°C for curing for 2h-3h, then the mold is removed, the edges are cut, and the surface is polished to 3000 mesh to obtain an inorganic artificial stone board with light-transmitting function, namely, light-transmitting artificial stone.
[0058] According to a sixth aspect of the present invention, there is provided a use of the above-mentioned light-transmitting artificial stone in architectural decoration.
[0059] The application of the light-transmitting artificial stone provided by the present invention is conducive to improving the decorative effect of buildings and can meet more decorative scene design requirements.
[0060] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0061] Example 1 A light-transmitting artificial stone is prepared by the following method: (1) Preparation of adhesive used for light-transmitting slurry: According to weight proportions, 10 parts of polymethyl methacrylate (PMMA), 2 parts of methyl acrylate, 45 parts of methyl methacrylate, 1 part of hydroxyethyl acrylate, 1 part of trimethylolpropane trimethacrylate and 0.02 parts of methyl ethyl ketone peroxide initiator were stirred and mixed to cause polymerization reaction, the stirring speed was set to 50 r / min, and the temperature was uniformly raised to 80°C at 3°C / min. When the viscosity of the obtained resin product reached 100 mPa.s, 0.01 parts of hydroquinone inhibitor was added, the stirring speed was set to 70 r / min, and the temperature was uniformly lowered to 30°C at 10°C / min to terminate the polymerization reaction, and stirring was continued for 30 minutes to obtain an adhesive; (2) Preparation of light-transmitting slurry: In parts by weight, 40 parts of the adhesive obtained in step (1), 5 parts of glass microspheres (translucent filler), 0.05 parts of diisocyanate, 0.05 parts of neopentyl glycol (shrinkage reducing agent), 0.05 parts of stearic acid (interface treatment agent), 0.05 parts of fatty alcohol polyoxyethylene ether sodium sulfate (penetrant), 0.01 parts of methyl ethyl ketone peroxide and 0.01 parts of 2-(2'-hydroxy-5'-methylphenyl) were added to a high-speed disc disperser at a speed of 150 r / min and stirred for 30 minutes to obtain a translucent slurry; (3) Preparation of translucent artificial stone: (a) preparing a matrix slurry by a discontinuous grading method, by weight, adding 40 parts of quartz sand of 26-40 mesh, 30 parts of quartz sand of 40-70 mesh, 3 parts of unsaturated polyester resin, 1 part of pigment, 0.04 parts of methyl ethyl ketone oxide and 0.04 parts of coupling agent (KH570) into a mixer and stirring for 3 minutes to obtain a matrix slurry; The obtained matrix slurry is evenly distributed on a mold with a frame, and then sent to a press for pressing (press parameters: vibration frequency 250Hz, vacuum degree 0.75bar, pressure 2MPa), and after pressing, a board embryo is obtained; (b) First, pour the light-transmitting slurry obtained in step (2) evenly on the surface of the board body, and then apply it evenly with a brush, and then put it into a press (which can be evacuated) or a vacuum box, turn on the vacuum pump, and perform vacuum treatment. Maintain the pressure at a vacuum degree of 0.75 bar for 2 minutes. The light-transmitting slurry will penetrate into the pores under the action of negative pressure, and the light-transmitting slurry spreading is completed; (c) After the light-transmitting slurry is applied, the board is placed at 100°C for curing for 2 hours, then the mold is removed, the edges are cut, and the surface is polished to 3000 mesh to obtain an inorganic artificial stone board with light-transmitting function, namely, light-transmitting artificial stone.
[0062] Example 2 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that in step (1), when the viscosity of the obtained resin product reaches 80 mPa.s during the preparation of the adhesive, a hydroquinone polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The remaining steps and process parameters are the same as those in Example 1.
[0063] Example 3 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that in step (1), when the viscosity of the obtained resin product reaches 150 mPa.s during the preparation of the adhesive, a hydroquinone polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The remaining steps and process parameters are the same as those in Example 1.
[0064] Example 4 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that, in step (3), when preparing the matrix slurry, the amount of the unsaturated polyester resin is 2 parts; The remaining steps and process parameters are the same as those in Example 1.
[0065] Example 5 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that, in step (3), when preparing the matrix slurry, the amount of the unsaturated polyester resin is 5 parts; The remaining steps and process parameters are the same as those in Example 1.
[0066] Example 6 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that in step (1), when the viscosity of the obtained resin product reaches 60 mPa.s during the preparation of the adhesive, a hydroquinone polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The remaining steps and process parameters are the same as those in Example 1.
[0067] Example 7 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that in step (1), when the viscosity of the obtained resin product reaches 180 mPa.s, a hydroquinone polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The remaining steps and process parameters are the same as those in Example 1.
[0068] Example 8 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that, in step (3), when preparing the matrix slurry, the amount of the unsaturated polyester resin is 1.5 parts; The remaining steps and process parameters are the same as those in Example 1.
[0069] Example 9 This embodiment provides a light-transmitting artificial stone and a preparation method thereof, which is different from the embodiment 1 only in that, in step (3), when preparing the matrix slurry, the amount of the unsaturated polyester resin is 6 parts; The remaining steps and process parameters are the same as those in Example 1.
[0070] Comparative Example 1 This comparative example provides a light-transmitting artificial stone and a preparation method thereof, which is different from Example 1 only in that, in step (2), no glass microbeads are added; The remaining steps and process parameters are the same as those in Example 1.
[0071] Comparative Example 2 This comparative example provides a light-transmitting artificial stone and a preparation method thereof, which is different from Example 1 only in that in step (2), no neopentyl glycol is added; The remaining steps and process parameters are the same as those in Example 1.
[0072] Comparative Example 3 This comparative example provides a light-transmitting artificial stone and a preparation method thereof, which is different from Example 1 only in that, in step (2), stearic acid is not added; The remaining steps and process parameters are the same as those in Example 1.
[0073] Comparative Example 4 This comparative example provides a light-transmitting artificial stone and a preparation method thereof, which is different from Example 1 only in that in step (2), no sodium fatty alcohol polyoxyethylene ether sulfate is added; The remaining steps and process parameters are the same as those in Example 1.
[0074] Test example The light-transmitting artificial stones obtained in the embodiments and comparative examples were tested, and the results are shown in Table 1.
[0075] Transmittance test method: polish the translucent area of the translucent artificial stone to a thickness of 20mm, polish both sides to 3000 mesh, cut into 100mm*100mm*20mm samples, use a transmittance meter to test the transmittance of the samples, and measure the transmittance data of the samples.
[0076] The flexural strength, linear expansion coefficient, and flexural strength loss rate after freeze-thaw cycles are tested according to the method in standard JG / T 463-2014 "Artificial quartz slabs for architectural decoration"; Among them, the bending strength loss rate after freeze-thaw cycle = (B1-B2) / B1*100%, B1 is the bending strength before freeze-thaw cycle, B2 is the bending strength after freeze-thaw cycle; freeze-thaw cycle test method, the test specimen is immersed in water for 48 hours and then subjected to freeze-thaw cycle, frozen at -20℃ for 4 hours, and immersed in 15℃ water for 4 hours as one cycle. After 25 cycles, the bending strength of the test specimen is the bending strength after freeze-thaw cycle.
[0077] Table 1
[0078] It can be seen from the data in Table 1 that the viscosity of the light-transmitting slurry has a great influence on the light-transmitting effect and the performance of the board. When the viscosity of the light-transmitting slurry is too low, the light-transmitting filler will have the problem of stratification and sedimentation, which will also affect the uniformity of the light-transmitting slurry, and will also produce large internal stress and affect the performance of the board; when the viscosity of the light-transmitting slurry is too high, there will be problems of holes and bubbles when filling the pores, which will further affect the light-transmitting performance and strength of the board; at the same time, adding an interface treatment agent to the light-transmitting slurry can significantly improve the adhesion between the light-transmitting slurry and the matrix material; adding a shrinkage-reducing agent to the light-transmitting slurry can effectively reduce the linear expansion coefficient of the light-transmitting slurry, avoiding the problem of thermal expansion and contraction due to temperature changes and the shedding or cracking of the matrix material; in addition, adding a penetrant to the light-transmitting slurry can improve the penetration ability of the light-transmitting slurry, making it easy to fill into the light-transmitting pore channels.
[0079] In summary, the method of the present invention is simple and convenient, and it only needs to fill the light-transmitting slurry into the connected pores on the upper and lower sides of the board. After high-temperature curing, the board can have light-transmitting properties. The light-transmitting slurry has basically no loss and high application efficiency, and the light-transmitting slurry can be quantitatively injected according to the porosity of the board. At the same time, the light-transmitting slurry of the present invention has good plasticity and can form a corresponding light-transmitting body according to the internal pore structure of the board. Therefore, the shape of the light-transmitting aperture is diversified and irregular, and the light-transmitting effect is more natural. In addition, the light-transmitting slurry is injected into the pores of the board after the board is pressed into shape, which effectively solves the problem of easy breaking, bending and displacement of the light-transmitting material in the prior art.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A light-transmitting slurry, characterized in that: The composition comprises the following components by weight: 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treatment agent, 0.05-0.2 parts of penetrant, and 0.01-0.05 parts of initiator; The adhesive is mainly prepared from the following components by weight: 5-20 parts of polymethyl methacrylate, 1-5 parts of methyl acrylate, 30-60 parts of methyl methacrylate, 1-5 parts of hydroxyethyl acrylate, 1-5 parts of trimethylolpropane trimethacrylate, and 0.01-0.05 parts of initiator; The preparation method of the adhesive comprises the following steps: The components are mixed in proportion to carry out polymerization reaction, and when the viscosity of the product obtained by the polymerization reaction reaches 80mpa.s-150mpa.s, a polymerization inhibitor is added to terminate the polymerization reaction to obtain the adhesive; The polymerization reaction temperature is 75°C-85°C; The polymerization inhibitor includes hydroquinone.
2. The light-transmitting slurry according to claim 1, characterized in that: The light-transmitting filler comprises at least one of glass microspheres and meteorological white carbon black; The shrinkage reducing agent includes neopentyl glycol; The interface treatment agent includes at least one of stearic acid, phthalate ester and phosphate ester; The penetrant includes at least one of sodium fatty alcohol polyoxyethylene ether sulfate, ammonium fatty alcohol polyoxyethylene ether sulfate and sodium lauryl sulfate; The initiator includes methyl ethyl ketone peroxide.
3. A method for preparing the light-transmitting slurry according to claim 1 or 2, characterized in that: The following steps are involved: By weight, 30-60 parts of adhesive, 5-10 parts of light-transmitting filler, 0.05-0.2 parts of shrinkage reducing agent, 0.05-0.2 parts of interface treating agent, 0.05-0.2 parts of penetrant and 0.01-0.05 parts of initiator are mixed to obtain the light-transmitting slurry.
4. Use of the light-transmitting slurry according to claim 1 or 2 in light-transmitting artificial stone.
5. A light-transmitting artificial stone, characterized in that: The light-transmitting slurry is prepared by using the light-transmitting slurry described in claim 1 or 2.
6. A method for preparing the light-transmitting artificial stone according to claim 5, characterized in that: The following steps are involved: (a) preparing a matrix slurry by a grading method, taking the matrix slurry for spreading, pressing, and obtaining an embryo body; The matrix slurry is prepared from the following components in parts by weight: 20-50 parts of quartz sand of 26-40 mesh, 20-50 parts of quartz sand of 40-70 mesh, 2-4 parts of unsaturated polyester resin, 1-5 parts of pigment, curing agent, and coupling agent; (b) spreading the light-transmitting slurry on the light-transmitting area of the embryo body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain the light-transmitting artificial stone.
7. The preparation method according to claim 6, characterized in that: The amount of the curing agent is 0.5%-2.0% of the amount of the unsaturated polyester resin; The amount of the coupling agent used is 0.5%-2.0% of the amount of the unsaturated polyester resin; The porosity of the artificial stone designed in the above-mentioned broken gradation mode is 10%-20%.
8. The preparation method according to claim 6, characterized in that: The light-transmitting slurry infiltrates and fills the pores in the light-transmitting area under the action of negative pressure; The curing temperature is 90° C.-110° C., and the curing time is 2 h-3 h.
9. Use of the light-transmitting artificial stone according to claim 5 in architectural decoration.
Citation Information
Patent Citations
Light-emitting water-permeable 3D printing concrete material and construction method thereof
CN116621544A
Light-transmitting inorganic artificial stone and preparation method thereof
CN118005344A
Composite solid surface article containing ocher
CN101072737A
Double-color artificial quartz stone and preparation method thereof
CN109485303A
Artificial stone and binder resin therefor
JP1994219800A
